2016
DOI: 10.1136/heartjnl-2015-308764
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing ventricular septal bulge versus hypertrophic cardiomyopathy in the elderly

Abstract: The burgeoning evidence of patients diagnosed with sigmoidal hypertrophic cardiomyopathy (HCM) later in life has revived the quest for distinctive features that may help discriminate it from more benign forms of isolated septal hypertrophy often labelled ventricular septal bulge (VSB). HCM is diagnosed less frequently than VSB at older ages, with a reversed female predominance. Most patients diagnosed with HCM at older ages suffer from hypertension, similar to those with VSB. A positive family history of HCM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…True sHCM is typically characterized by reverse curve septal hypertrophy representing the majority of sHCM cases in our study. This phenotype should be distinguished from isolated sigmoid hypertrophy of the basal septum, which represents a more benign form and is often no true primary HCM (51).…”
Section: Limitationsmentioning
confidence: 99%
“…True sHCM is typically characterized by reverse curve septal hypertrophy representing the majority of sHCM cases in our study. This phenotype should be distinguished from isolated sigmoid hypertrophy of the basal septum, which represents a more benign form and is often no true primary HCM (51).…”
Section: Limitationsmentioning
confidence: 99%
“…A sigmoid septum (also denoted as ventricular septal bulge or angled aorta) is considered a normal variant or a minor abnormality often encountered in echocardiographic examinations of the elderly [12][13][14][15]23]. Sometimes, distinguishing between the SS and hypertrophic cardiomyopathy can be problematic because SS can cause an LV outflow tract obstruction [24][25][26][27][28]. It has been also reported that subjects with SS more frequently have hypertension, greater relative wall thickness, and LV diastolic dysfunction [15,23,30].…”
Section: Impact Of Sigmoid Septum On Rv Shapementioning
confidence: 99%
“…A recent review suggests an algorithm for differentiating what the authors term “ventricular septal bulge” (VSB) from HCM. The proposed entry criteria are BSH>1.2 cm and ratio of basal to mid‐septal thickness ≄1.5 cm.…”
Section: Recommendations On the Clinical Approach To Patients With Bshmentioning
confidence: 99%